Muppets in Moscow : the unexpected crazy true story of making Sesame Street in Russia - Lance Rogoff, Natasha (Rowman & Littlefield, 2022)
"Muppets In Moscow reveals how-in between bombings and political chaos in 1990s Moscow-a team of Russian and American artists, producers, educators, writers, and puppeteers overcame their many differences to create an unprecedented hit in a post-communist era"--